Menopausal estrogen therapy and non‐Hodgkin's lymphoma: A post‐hoc analysis of women's health initiative randomized clinical trial. Issue 3 (14th September 2015) - Kato, Ikuko; Chlebowski, Rowan T.; Hou, Lifang; Wactawski‐Wende, Jean; Ray, Roberta M.; Abrams, Judith; Bock, Cathryn; Desai, Pinkal; Simon, Michael S
Abstract : Estrogens are important immunomodulators, exerting significant effects on cell proliferation, apoptosis, cytokine production and differentiation of hematopoietic cells. Estrogen receptors are expressed on normal B and T lymphocytes, bone marrow and in leukemia and lymphoma cell lines. Epidemiologic evidence for the association of menopausal hormone use with risk of non‐Hodgkin's lymphoma (NHL) has been mixed; however, all of the investigations have been observational. We analyzed the data from Women's Health Initiative hormone therapy trials where conjugated equine estrogens (CEE; 0.625 mg/d) plus medroxyprogesterone acetate (MPA; 2.5 mg/d) ( n = 16, 654) or CEE alone (women with prior hysterectomy) ( n = 10, 685) were tested against placebos and the intervention lasted a median of 5.6 years in the CEE + MPA trial and 7.2 years in the CEE alone trial. During 13 years of follow‐up through September 20, 2013 383 incident NHL cases were identified. We used the intent‐to‐treat approach to calculate incidence rates of NHL, hazards ratios (HR) and 95% confidence intervals (CI) by treatment group. Incidence of NHL was virtually the same in the treatment and placebo groups. The HR was 1.02 (95%CI 0.74–1.39) for CEE alone, 0.98 (95% CI 0.76–1.28) for CEE+MPA, and 1.00 (95% CI 0.82–1.22) for both combined. There were no specific NHL subtypes associated with either type of the treatment, except a marginally decreased risk of plasma cell neoplasms (HR= 0.53 95% CI 0.27–1.03) in the CEE‐alone group. These results do not support a role of estrogen alone or combined with progestin in the development of NHL among postmenopausal women. Abstract : What's new? Non‐Hodgkin lymphoma (NHL) is linked etiologically to disrupted immune function, and in women, that disruption may be attributed in part to the immunomodulatory activities of estrogens. Here, the relationship between estrogen and NHL was explored in a randomized clinical trial of postmenopausal women on hormone therapy that consisted of either estrogen alone or estrogen plus progesterone. NHL incidence rate was about the same for women taking either form of hormone therapy. Women taking only estrogen experienced a modest reduction in risk of plasma cell neoplasm. Overall, the findings suggest that NHL risk is largely unaffected by estrogens.